ARTIFICIAL BREEDING OF CLARIAS BATRACHUS - BORDOLOI, R. (Journal of the Inland Fisheries Society of India, 2021)
Several workers attempted breeding and rearing of Clarias batrachus in India and abroad. Mookerjee et al , (1950 ) studied some aspects of the life history of C. batrachus; Ramaswami and Sundararaj (1957) on induced spawning of Clarias; Tongsanga et al., (1963) worked on induced spawning in catfish, C. macroce, by pituitary hormone injection; Sidthimunka et al (1968) on the culture of catfish (Clarias sp.) in Thailand. Devaraj et al. (1972) worked on induced breeding of freshwater catfish, Clarias batrachus (Linn.) by using pituitary glands from marine catfish and Khan et al. (1975) studied stocking material of some air breathing fishes by hypophysation in India.and Thakur (1976) studied the spawning behavior of C. batrachus.